2020
DOI: 10.4103/jehp.jehp_643_19
|View full text |Cite
|
Sign up to set email alerts
|

A systematized review of cognitive load theory in health sciences education and a perspective from cognitive neuroscience

Abstract: INTRODUCTION: To design instructions in health sciences education, it is highly relevant to heed the working memory and the approaches for managing cognitive load. In this article, we tried to mention the implications of cognitive load theory (CLT) for optimizing teaching-learning in health sciences education and discussing cognitive load from the perspective of cognitive neurosciences as brain-aware medical education. MATERIALS AND METHODS: We searched databases of Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…This research has shown that bystanders are often hesitant to provide interventions such as dispatcher-assisted CPR because they fear for their personal safety, doubt their ability to intervene effectively, or are overwhelmed in the face of heavy cognitive load. 18 , 19 , 20 , 21 Our work augments this existing literature by showing that bystanders with no relevant expertise are able to overcome these barriers even while interacting with an unfamiliar piece of medical technology. Our simulations also strongly demonstrated the importance of anticipating and limiting the cognitive load placed on lay rescuers.…”
Section: Discussionmentioning
confidence: 70%
“…This research has shown that bystanders are often hesitant to provide interventions such as dispatcher-assisted CPR because they fear for their personal safety, doubt their ability to intervene effectively, or are overwhelmed in the face of heavy cognitive load. 18 , 19 , 20 , 21 Our work augments this existing literature by showing that bystanders with no relevant expertise are able to overcome these barriers even while interacting with an unfamiliar piece of medical technology. Our simulations also strongly demonstrated the importance of anticipating and limiting the cognitive load placed on lay rescuers.…”
Section: Discussionmentioning
confidence: 70%
“…PMR, by alleviating cognitive and emotional stressors, may reduce extraneous cognitive load. This could improve learning efficiency and optimize cognitive resource utilization (Debue and Van De Leemput, 2014 ; Ghanbari et al, 2020 ; Kastaun et al, 2021 ). For instance, a medical student grappling with complex diagnostic protocols could find that regular PMR practice helps manage the cognitive overload, making learning more manageable and effective.…”
Section: Discussionmentioning
confidence: 99%
“…Germane cognitive load is the mental effort put into the acquisition/development of schemas of information to be held in long-term memory. To optimize learning, educators are encouraged to manage intrinsic cognitive load, minimize extraneous cognitive load, and promote germane cognitive load ( 10 ). High scores on the germane cognitive load (self-perceived learning) scale have been reported to be predictive of higher academic performance ( 11 ).…”
Section: Introductionmentioning
confidence: 99%